Dichotomous Sirtuins: Implications for Drug Discovery in Neurodegenerative and Cardiometabolic Diseases - Gomes, Pedro (2019)
Sirtuins (SIRT1-7), a class of NAD+-dependent deacylases, are central regulators of metabolic homeostasis and stress responses. While numerous salutary effects associated with sirtuin activation, especially SIRT1, are well documented, other reports show health benefits resulting from sirtuin inhibition. Furthermore, conflicting findings have been obtained regarding the pathophysiological role of specific sirtuin isoforms, suggesting that sirtuins act as 'double-edged swords'. Here, we provide an integrated overview of the different findings on the role of mammalian sirtuins in neurodegenerative and cardiometabolic disorders and attempt to dissect the reasons behind these different effects. Finally, we discuss how addressing these obstacles may provide a better understanding of the complex sirtuin biology and improve the likelihood of identifying effective and selective drug targets for a variety of human disorders.